1997
DOI: 10.1128/iai.65.9.3875-3881.1997
|View full text |Cite
|
Sign up to set email alerts
|

Fimbriae and the hemagglutinating adhesin HA-Ag2 mediate adhesion of Porphyromonas gingivalis to epithelial cells

Abstract: The mechanisms by which Porphyromonas gingivalis, a gram-negative anaerobic bacterium, is pathogenic for the periodontium remain largely hypothetical. Invasion of host tissues by P. gingivalis is believed to require adhesion of the bacterium to host cells. The aim of this study was to use monoclonal antibodies (MAbs) to characterize the bacterial cell surface component(s) acting as a ligand binding to a receptor on epithelial cells. Surface antigens of P. gingivalis ATCC 33277 were obtained as a glass bead-EDT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The 33 and 38 kDa HA-Ag2 proteins were extracted using an EDTA containing buffer whereas the 43 and 49 kDa forms were isolated from extracellular vesicles. Spe-ci®c antibodies to HA-Ag2 have been shown to inhibit haemagglutination and binding of P. gingivalis to epithelial cells (28,49,315). A number of studies have identi®ed four P. gingivalis genes that encode haemagglutinin proteins HagA, B, C, and D (191,192,278,279).…”
Section: Haemagglutininsmentioning
confidence: 99%
“…The 33 and 38 kDa HA-Ag2 proteins were extracted using an EDTA containing buffer whereas the 43 and 49 kDa forms were isolated from extracellular vesicles. Spe-ci®c antibodies to HA-Ag2 have been shown to inhibit haemagglutination and binding of P. gingivalis to epithelial cells (28,49,315). A number of studies have identi®ed four P. gingivalis genes that encode haemagglutinin proteins HagA, B, C, and D (191,192,278,279).…”
Section: Haemagglutininsmentioning
confidence: 99%
“…2,3,5 This has been attributed to differences between their surface characteristics. 2,7,8 The presence of fimbriae seems important, as decreased adhesion capacity is seen for fimbriae-deficient mutants of P. gingivalis 9 and when specific antibodies against fimbriae are applied prior to adhesion assays. 7 Different capsular serotypes are known for P. gingivalis.…”
mentioning
confidence: 99%
“…2,7,8 The presence of fimbriae seems important, as decreased adhesion capacity is seen for fimbriae-deficient mutants of P. gingivalis 9 and when specific antibodies against fimbriae are applied prior to adhesion assays. 7 Different capsular serotypes are known for P. gingivalis. 10 In addition to a non-encapsulated type, 6 different capsular (K) serotypes have been described for P. gingivalis.…”
mentioning
confidence: 99%
“…Porphyromonas gingivalis fimbriae are important cell structures involved in adherence of the bacterium to periodontal tissues and may also be important in other virulence properties of this organism (6,9,14). Many investigators have demonstrated the infiltration of monocytes/macrophages into periodontal tissues of individuals with adult periodontal disease, a chronic inflammatory disease (8,19,22).…”
mentioning
confidence: 99%